The Revised Book VI, Part I Selected Norms and Commentary - Austin, Brian T. ca. 20./21. Jh. (The jurist, 2021)
This study comments upon selected norms of Part I ("Delicts and Penalties in General") of the revised Book VI ("Penal Sanctions in the Church") of the Latin code. The revised text places a greater emphasis on the demands of justice and the necessity of having recourse to the penal system, balanced by principles such as the presumption of innocence and the right of defense. Substantive changes are presented in a tabular format for ease of comparison with former disciplines and schemata, with a particular focus on style and Latinity. Most significantly, the institute of prescription has been clarified, the scope of censures (in particular, that of interdict) broadened, and expiatory penalties made more determinate. The study concludes with an overall summary and initial assessment of Part I of the revised text.